The Gospel of Matthew; v.2 chapters 12 to 28 - Barclay, William, 1907-78 (Condell Park, NSW Christian Press, 1988)
Includes bibliographical references.
Originally published: Edinburgh, Scotland, St Andrew Press, 1957. Rev. ed. published by same, 1975.
Keywords: Bible. N.T. Matthew, XI-XXVIII -- commentaries